(untitled) (Al-Qantara, 2024)
This study explores the concept of Green Human Resource Management (Green HRM) and its impact on manufacturing firms in Sri Lanka. Green HRM integrates eco-conscious practices into HR policies to enhance sustainability and environmental performance. It focuses on strategies such as green recruitment, training, performance management, and employee engagement to foster a culture of environmental responsibility. In the Sri Lankan manufacturing sector, Green HRM has been shown to improve environmental compliance, reduce operational costs, enhance corporate reputation, and promote innovation. Despite these benefits, the implementation of Green HRM faces challenges, including financial constraints, limited awareness, and resistance to change. This abstract emphasizes the need for government support, public-private partnerships, and targeted awareness programs to address these barriers. The findings suggest that Green HRM not only contributes to sustainable business practices but also positions Sri Lankan manufacturing firms for enhanced competitiveness in global markets.